How Much Time Should Be Waited and What Are the Main Findings to Evaluate the Hepatocellular Carcinoma Response to Regorafenib? A Real-Life Experience - Gustavo Hideki Kawanami; Leopoldo Katsuda; Thiara Barcelos Rocha; Fabio da Silva Yamashiro; Leonardo Pelafsky; Xingshun Qi; Fernando Gomes Romeiro (Canadian Journal of Gastroenterology and Hepatology)
Background. Hepatocellular carcinoma is a relevant cause of mortality worldwide, mainly among patients who have a prior liver disease. In spite of clear recommendations regarding surveillance and screening methods, most patients are still diagnosed only when they are no longer candidates to curative treatment modalities, while others do not achieve the goals of such treatments, thus increasing the need of anticancer drugs. Moreover, when cirrhotic patients begin to receive these drugs, many types of adverse events are seen as a reason to withdrawal, even when there are findings suggesting a good response to the treatment. Case Summary. This case report is about a cirrhotic patient who received many types of treatment, from surgery and chemoembolization during early stages to first- and second-line systemic therapy when the disease turned to be advanced. Since he had no signs of liver dysfunction and suffered tumor progression during sorafenib treatment, regorafenib was initiated. The main findings that make this case important are the adverse events after taking this second-line agent, which would certainly be considered unacceptable and would lead to the drug withdrawal. The reasons why regorafenib was maintained are explained based on clinical and imaging findings, showing how this decision led to an excellent response. Conclusions. The knowledge of the main adverse events described in the pilot clinical trials can avoid unnecessary withdrawal of regorafenib. In addition, some clinical and imaging findings can be deemed as predictors of good response to tyrosine kinase inhibitors.